Nghiên cứu bạch cầu cấp với những kiểu hình miễn dịch ít gặp - Tuý, Trần Thị Phương; Thăng, Nguyễn Duy; Tránh, Nguyễn Văn; Hạnh, Nguyễn Thị Hồng; Hoa, Phan Thị Thùy; Cương, Ngô Tứ; Vũ, Trần Ngọc; Thanh, Bùi Thị Thu; Lan, Hà Thị Phương; Hiền, Nguyễn Thị Thu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.